Pembelajaran Ekonomi Generasi Z Di Masa Pandemi Covid-19 - Ana Dhaoud Daroin; Dwi Nila Andriani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2021)
The objectives of this study are 1) Analyze the appropriate form of economic learning for generation Z; 2) Describe the appropriate learning techniques in the pandemic era for generation Z; 3) Compare the economic learning patterns before and after the Covid 19 pandemic;. The research method used is qualitative, with a descriptive approach using case studies in junior high schools (SMP), high schools (SMA) and universities in East Java province. The results show that 1) the right form of learning in generation Z is learning that utilizes digital technology whether it is carried out online, offline or blended learning. 2) Learning techniques in the pandemic era for generation Z are through recording, individual assignments ( self observation), projects / works, quizzes, live books, and group assignments. 3) Comparison of economic learning before the pandemic was carried out directly, while online-based economic learning after the Covid 19 pandemic was mostly conducted through the Learning Management System (LMS) and video conferencing. DOI: https://dx.doi.org/10.17977/UM014v14i12021p86